The price effects of cash versus in-kind transfers - Jesse M. Cunha; Giacomo De Giorgi; Seema Jayachandran (Federal Reserve Bank of New York, 2015)
This paper examines the effect of cash versus in-kind transfers on local prices. Both types of transfers increase the demand for normal goods; in-kind transfers also increase supply in recipient communities, which should cause prices to fall relative to cash transfers. We test and confirm this prediction using a program in Mexico that randomly assigned villages to receive boxes of food (trucked into the village), equivalently valued cash transfers, or no transfers. We find that prices are significantly lower under in-kind transfers compared with cash transfers; relative to the control group, in-kind transfers lead to a 4 percent fall in prices while cash transfers lead to a positive but negligible increase in prices. Prices of goods other than those transferred are also affected, but by a small amount. Thus, households' purchasing power is only modestly affected by these price effects, even in this setting where program eligibility is high, the transfer per household is sizeable, and hence the supply influx is large. The exception is in remote villages, where the price effects (both the negative effects of in-kind transfers and the positive effects of cash transfers) are larger in magnitude. The effects do not dissipate over the two years of program duration we observe.
Keywords: O12; O00; 330; price; policy